Understanding eating disorder symptoms in same-gender couples: social environmental factors - Diane L. Rosenbaum; Kristin J. August; Meghan M. Gillen; Charlotte H. Markey (Journal of Eating Disorders, 2023)
Plain English summary Sexual minority individuals are at disproportionately greater risk for eating disorders, yet little is known about the ways in which factors in the social environment relate to eating disorder symptoms in this population. This research investigates sociocultural attitudes and romantic relationship quality as factors in the social environment in relation to eating disorder symptoms for men and women in same-gender relationships. We found differences in the occurrence of eating disorder symptoms, such that sexual minority men had more uncontrolled eating compared to sexual minority women. Across all participants, internalization of sociocultural attitudes was linked to greater disordered eating symptoms. We also investigated a potential buffering role of a romantic partner on eating disorder symptoms, and found that high quality, committed, romantic relationships were beneficially associated with less uncontrolled eating for sexual minority men.